A survey on the parental attitudes toward the educational upliftment of their children and child-rearing styles in Barangay Canipaan, Hinunangan, Southern Leyte - Bastes, Rosanna Sumayo (Tacloban City Rosanna Sumayo Bastes, 1999)
With parents putting a high premium on the education of their children, relentless campaign was launched for giving the quality of existence and conditions antecedent for them to become progressive, peaceful and dynamic participants in the process of nation-building.
A survey was conducted to investigate the attitudes of parents toward the educational upliftment of their children and their child-rearing styles they implemented.
This study was conducted among 30 parents of Grade Two Pupils enrolled at Canipaan Elementary School during the School Year 1998-1999. The data were gathered by means of an interview schedule or questionnaire.
The findings of the study showed that majority of the parent-respondents practiced democratic-egalitarian style but they have indifferent attitude towards the educational upliftment of their children.
Keywords: Parental Rearing Instrument; Parental attitudes; Education-centered concepts; Social Science